Correlation of Age at Menarche and Nutritional Status with Age at Menopause: Implications for Women's Reproductive Health - Nurhidaya Aya; Dwi Ghita (Ammar Dharma Foundation, 2025)
Background: Menopause is a period when menstruation naturally stops or a time when a woman experiences her last menstrual bleeding and never menstruates again .Objective: To determine the factors related to the age of menopause, identification was carried out by grouping menopausal women based on the age of menarche and nutritional status.Methods: The research method is analytical with a cross-sectional study approach using primary data from 90 menopausal women. Data were analyzed using qualitative descriptive research . The sampling technique used in this study was purposive sampling.Results: The results of the study showed that in the menarche age indicator , the calculated Chi Square was greater than the Chi Square table (17.83 > 3.841) so Ha was accepted and Ho was rejected so that there was a relationship between the age of menarche and the age of menopause. In the nutritional status indicator, the calculated Chi Square was greater than the Chi Square table (17.2 > 3.841) , so Ha was accepted and Ho was rejected so that there was a relationship between nutritional status and the age of menopause.Conclusion: In conclusion , namely There is a relationship between the age of menarche and the age of menopause and there is a relationship between nutritional status and the age of menopause, so there needs to be information or counseling for the community about factors related to the age of menopause and especially factors that can accelerate menopause.